Medication-Related Burden among Iraqi Patients with Crohn’s Disease: A Cross Sectional Study - Nawar Abdulridha Abood; Dheyaa J. Kadhim; Raghad Jawad Hussein (Iraqi Journal of Pharmaceutical Sciences)
Crohn’s disease is an inflammatory bowel disease that is characterized by chronic inflammation of any part of the gastrointestinal tract, has a progressive and destructive course and is increasing in incidence worldwide. Medical treatment of Crohn’s disease is usually divided into remission induction therapy and remission maintenance therapy. Medication-related burden is a new concept focused on the negative experiences resulting from taking medicines. The aims of the current study were to measure medication-related burden among a sample of Iraqi patients with Crohn’s disease, and to determine any associations between medication-related burden and some patient factors. The present study was cross-sectional conducted at ‟Gastroenterology and Hepatology Teaching Hospital/ Medical City / Baghdad / Iraq” during December 2022 to May 2023. The Arabic version of living with medicine questionnaire was used to measure medication-related burden experienced by the patients. 94 Crohn’s disease were included [Males =58 (61.7%), Females=36 (38.3%)] with mean age (31.9‎±‎10.8 years). The mean of total burden score was (102.7 ± 20.6) with more than half (54.3%) of the patients experienced a minimum degree of medication burden, followed by moderate burden (29.8%), no burden (8.5%) and high burden (7.4%). Three domains showed the highest mean of burden scores:  “Cost Related Burden”, “concerns about medicines use” and “Autonomy to vary regimen”. Total burden score, “side effects of medicines” and “effectiveness of prescribed medications” domains were significantly lower in remission patients compared to active cases. In conclusion, a large proportion of the Crohn’s disease have experienced varying degrees of medication-related burden. Disease  activity was independently correlated with total burden score.